(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
The need for extend the urban horticulture to cover the food security demands, to mitigate CO2 emissions and avoid the extreme heat waves drive this study to investigate the ability of using soilless culture systems, vermicomposting technology and net cover in producing vegetables in urban area in summer season. The aim of this study was to determine the effect of different vermicompost rates mixed with the standard substrate peat moss: perlite (perlite: peat moss: vermicompost (45:45:10) (Mix.10%), perlite: peat moss: vermicompost (40:40:20) (Mix.20%), perlite: peat moss: vermicompost (35:35:30) (Mix.30%) and perlite: peat moss (50:50 V/V) (Control) under three microclimate conditions (plants covered with black net, white net and without cover) on vegetative growth and yield of sweet pepper (Capsicum annuum L. cv. Reda) grown in pots culture during summer seasons of 2012 and 2013 at the Central Laboratory for Agricultural Climate, Agricultural Research Center, Dokki, Giza Governorate. Physical and chemical properties of substrates, vegetative growth and yield characteristics, agrometerological data and mineral contents were determined. The obtained data indicated that vermicomposting could contribute in mitigate CO2 emission, save the essential nutrients and energy via recycling the urban organic wastes to vermicompost. The physical and chemical properties were affected by vermicompost. The best vegetative growth and yield of sweet pepper were given by (Mix.20%) vermicompost mixture followed by (Mix.10%) and (Mix.30%) vermicompost mixture. There were also significant differences between cover net treatments in affecting vegetative growth and yield of pepper, the white net was superior for producing pepper during the summer season; while the black net gave the lowest plant growth and yield. The best treatment was (Mix.20%) vermicompost mixture with white net cover, while the lowest vegetative growth and yield were obtained by (Control) vermicompost mixture with black cover net during the two tested seasons. These results suggested that vermicomposting and green roof can be used in urban area for producing food instead of incineration the urban organic wastes or imported food from rural area and using white cover net to improve the pepper growth and productivity during summer season.